Rancang Bangun Aplikasi Pelaporan Muatan Ekspedisi Pada PT. Timu Rayasakti Probolinggo - Dhany, Umar; Sulistiowati, Sulistiowati; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT. Timu RayaSakti Probolinggo is a pioneer company / pioneer in the field of timber shipping expedition Gaharu wood in Probolinggo City. PT. Timu RayaSakti Probolinggo during the process of reporting their daily activities are still using manual methods, such as recording transactions, document storage, making reports, and memoranda piled up going to lose notes and documents. To overcome the above problems, it created a plan to build cargo expedition reporting application that can automate the reporting process at PT. Timu RayaSakti Probolinggo, an application used to manage processes ranging from customer data processing, order transaction, and report generation. The results of the design load reporting applications expedition is expedition reports. In conclusion, the design application expedition cargo reporting helps employers to manage transaction data and can generate reports to help monitor the business owner.Keywords: application, sales Information System Reporting